The Role of Information and Communication Technology in Advancing Sustainable Energy Transition in Developing Countries: Progress, Opportunities and Challenges - Yusak Tanoto (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2024)
Sustainable energy transitions in developing countries are critical for balancing economic growth and environmental sustainability. Transitioning to renewable energy sources alleviates energy poverty and reduces reliance on fossil fuels. Information and communication technology (ICT) plays an important role in advancing the energy transition and achieving low-carbon energy utilization by facilitating the transition of power sectors to renewable energy sources. This paper provides an overview of the role of ICT in achieving sustainable energy transition in developing countries and jurisdictions. It emphasises the significance of SDG 7 and other sustainable energy transition indices for energy access and transition, as well as presenting their status and progress in various regions, including developing countries. This paper also discusses several types of available ICT tools and methods that enable digitalization in the power sector, such as smart grids, smart metres, energy management systems, Internet of Things (IoT) for energy, and renewable energy monitoring systems, as well as the opportunities and challenges of incorporating ICT into the context of developing countries' sustainable power sector.